Permeability in education, vocational training and further education - the key to lifelong learning : Expertise ; Presidency Conference "Realizing the European Learning Area", Munich, 4-5 June 2007 - Freitag, Walburga [Verfasser] (My University, 2007)
"The central function of prior learning recognition as a learning pathway to Higher Education (HE) is to set up frameworks so that learning - regardless of where and how it has been acquired - can be identified, assessed and recognized as equivalent to required learning outcomes of a specific course in HE. The concept is perceived as a key to increase permeability in education systems and hereby social inclusion, as well as an important strategy to reduce the effects of demographic changes." The first chapter takes a closer look at the different approaches of the "concept of prior learning recognition", which can be characterized not only in terms of cultural background but also in terms of the main field they are related to or developed by (vocational training, higher education, labour market) and in terms of the purposes they are developed for (personal development, gaining access, individual credit transfer, structured credit transfer, advanced standing in a programme). The second chapter gives an overview of different approaches concerning the implementation of the APL, APEL and WBL traced in selected EU Member States (United Kingdom, France, Norway, Denmark, Sweden, Finland, Netherlands, Estonia, Slovenia, and Germany). In the fourth chapter the contribution of National Qualifications Frameworks (NQFs) and Credit transfer systems for the implementation of prior learning accreditation is regarded. The closing chapter summarizes the visible effects in Europe through implementation of APL for intersectoral credit transfer, which refer according to the author to the following three areas: increasing professionalization of APL; positive effects on learning in HE in general; increasing the knowledge transfer between education sectors, the 'world of work' and HE. (Autorenreferat, BIBB-Doku)
Keywords: G 2.5.3 Anschlussfähigkeit von Bildungsgängen; S 2.2.4 Anrechnung, Prüfung & Zertifizierung; I 2.2 Europa; Durchlässigkeit im Bildungssystem; Berufsbildung; Hochschulbildung; Anrechnung von Bildungsleistungen; Qualifikationsrahmen; Leistungspunktesystem; Europa